Critical Success Factor for Labuhan Bajo Airport Public-Private Partnership Investment Pilot Project - Irma Yusfida (Faculty of Engineering, Andi Djemma University, 2022)
The government often faces budget constraints and financial gaps between necessity and real allocation funds. It makes them must be more selective when prioritizing infrastructure development. Moreover, providing adequate transport infrastructure and sustainability is crucial for the government. Government must innovate by creating a conducive investment climate to encourage the participation of private and state-owned enterprises in infrastructure financing. Innovation financing through Private Funding and PPP schemes is directed to infrastructure with high economic and financial feasibility. PPP schemes in the air transportation sector particularly in Indonesia have not been successfully implemented until 2018. Therefore, the government has initiated several PPP projects as pilot projects to encourage PPP implementation in the Transportation Sector. One of them is Labuan Bajo International Airport. Labuan Bajo Airport is in West Manggarai Regency as a gateway to enter the Komodo Island area. Labuan Bajo airport is one key infrastructure that supports The Big 5 Super Priority Destinations of Indonesia by the Indonesia Ministry of Tourism and Creative Economy. This paper aims to examine critical success factors and interfere factors of the PPP pilot project for Labuan Bajo Airport. This paper uses an exploratory descriptive method to examine every factor that supports the success of the PPP implementation process in the air transportation sector based on qualitative data. The study will also explore the planning process through analysis of PPP Book documents from 2010-2020 (content analysis) to historically examine the process of proposing PPP project activities and examine the factors that support the success or delay the PPP pilot project within the Ministry of Transportation based on stakeholder approach. The planning and preparation stage plays a critical role in efforts to prepare comprehensive, reliable, and feasible projects. The feasible project can minimize project uncertainty and gain attract private sector investment.